Applicability of Model Assessment for Learning (AFL) in Classes of Vocabulary and Pragmatics in English Teaching Learning at STAIN Salatiga - Woro Retnaningsih (IAIN Salatiga, 2013)
The research objective is to see the applicability of Assessment for Learning (AFL) in the classes of vocabulary and pragmatics. The subjects of the research were students and lecturers of Vocabulary 3 and Pragmatics classes. The research was conducted in State Islamic Studies Institute (STAIN) Salatiga, Central Java, Indonesia. The results of theresearch indicate that AfL could assess the class activities comprehensively. It could assess teacher and students‘ behavior in the class. The teacher guides the class from preparing the class, delivering materials and evaluating the class. Meanwhile students‘ behavior in theclasses of pragmatics is better then in vocabulary. Students who express positive behavior in the classes of vocabulary are in the range of 30% - 60% and around 80 – 90s % in pragmatics.Keywords: assessment for learning; evaluation; vocabulary; pragmatics; English teaching learning